Hipertonia dos músculos do assoalho pélvico em mulheres: Ocorrência e fatores que influenciam - Ana Paula Goncalves Miranda (2018)
Muscle tone is the tension that exists in the skeletal muscles at rest. It results from the structural and physiological characteristics of and from the demands on the neuromuscular system. Hypertonia, the increase of muscle tension at rest, is a frequent finding in clinical practice and, when found on pelvic floor muscles (PFM), it appears to be associated with various symptoms of pelvic floor dysfunction. It also appears to be associated with other PF muscle impairments, such as relaxation and strength impairment. In addition to compromising the functions of the pelvic organs, PFM impairment may compromise the lumbopelvic stabilization mechanism and favor the occurrence of low back pain. Furthermore, personal factors such as stress, that lead to hipertonia of muscles in the central regions of the body, also appear to be associated with PFM hipertonia. However, literature on the subject presents a wide conceptual and operational variation of hipertonia, leading to uncertainties about its actual prevalence in the PFM of women, on the associated factors and, ultimately, on the effectiveness of treatment. Objectives: The objectives of this study were: (i) to document the occurrence of PFM hipertonia on women; (ii) to investigate the relationship between PFM hipertonia and the following functional factors: Local musculoskeletal (MS) (muscle and sensorial functions of the PF: proprioception, pain, reaction during cough, capacity for contraction and relaxation, coordination, strength and resistance), neuromuscular activity at rest and at maximal contraction, and at rest vaginal pressure; global MS factores (pelvic stability and lumbopelvic pain), and the personal factor stress, (iii) and identify the functional factors that best explain the occurrence of PFM hipertonia in women. Methods: This was a cross-sectional study that investigated women in the community. First, an interview was conducted to characterize the sample regarding personal and clinical factors, personal stress and severity of musculoskeletal pain. Then, the physical, sensory, muscular and physiological functions of the pelvic floor muscles were evaluated through the Pelvic Floor Sensory and Muscular Functions Examination (EFSMAP) and electromyography, and, finally, pelvic stability was evaluated through the Bridge Test. Women over 18 years of age who had had intercourse before were considered eligible for the present study. For data analyses, the participants were categorized as Hyper when they presented hipertonia of the PFM or as NormoHipo when they presented normal or hypotonic tone, that is, without hipertonia of the PFM. Descriptive statistics characterized the sample according to sociodemographic data and the presence of genitourinary and defecation impairment. The association between local MS and global MS potential impairments and stress was tested using Logistic Regression with a level of significance of 5%. Results: From a sample calculation, one hundred and twenty women were included in the study. Of these, 33.3% presented PFM hipertonia. The hipertonia was shown to be related to local and global MS factors and to personal stress, with local MS factors being what best explained the occurrence of PFM hipertonia. Conclusion: The results of this study reinforce the hypothesis that PFM hipertonia is a mechanism of adaptation of the neuromuscular system to functional demands and reinforces the need to further investigate this mechanism. In addition, this study helps physiotherapists in Women's Health to direct clinical reasoning during evaluation, rehabilitation and preventive approach to women with PFM hipertonia.